2016
DOI: 10.1080/10511970.2016.1194341
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of a Mathematics Major for Prospective Elementary Teachers with an Inquiry‐Based Philosophy

Abstract: In this paper we present data from one-on-one interviews conducted with students who have taken intermediate and advanced inquiry-based mathematics courses in a program that prepares future preK-8 teachers. Many of these students entered college with a fear of math but then gained confidence from a required introductory math course and chose to pursue a major in Mathematics for Teaching. These interviews help explain their choice to pursue this major and their general experiences in IBL math classes. These ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…First, all of the papers in Part I contain further ideas for implementing inquiry. They give particularly detailed insight into the daily workings of their classrooms [3,11,13,14] and ideas about implementing courses for future teachers [3,5,10,12], a population that is not represented here in Part II. Moreove0r, they explicitly discuss courses for students not majoring in mathematics [4,11,13], revealing connections between mathematical inquiry and inquiry in other disciplines and further clarifying the nature of inquiry.…”
Section: Implementing Inquirymentioning
confidence: 99%
“…First, all of the papers in Part I contain further ideas for implementing inquiry. They give particularly detailed insight into the daily workings of their classrooms [3,11,13,14] and ideas about implementing courses for future teachers [3,5,10,12], a population that is not represented here in Part II. Moreove0r, they explicitly discuss courses for students not majoring in mathematics [4,11,13], revealing connections between mathematical inquiry and inquiry in other disciplines and further clarifying the nature of inquiry.…”
Section: Implementing Inquirymentioning
confidence: 99%
“…To further complicate matters, scholars have identified a variety of trusting relationships as necessary antecedents to successfully facilitate IBL in higher education (hereafter referred to as "IBL-HE") including mutual trust between the students (particularly when group work is involved), students and/instructors, instructors and administration, and trust in the pedagogy itself are important (Boyle & MacKinnon, 2016;Cook & Borkovitz, 2017;Cooper, Bailey, Briggs, & Holliday, 2017;Cuneo et al, 2012;Harvie, Harper-Tavers & Jaeger, 2017;Justice et al, 2009;Love et al, 2015;MacKinnon, 2017;Yang, 2015). Research on how to develop and maintain these types of trust in higher education settings, particularly when instructors and students are attempting to step outside their comfort zones and engage in IBL however, is sparse (Aditomo, Goodyear, Bliuc, & Ellis, 2013;Beltrano, Archer-Kuhn, & MacKinnon (under review); Friesen & Scott, 2013;Risley & Petroff, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the student enjoyed the problem-posing process, which involved asking why things occur the way that they do. Along the lines of discovering reasons and asking why, Cook and Borkovitz (2017) found that inquiry learning led to more confidence in mathematics and an increased ability when solving problems for a mathematics major. The student attributed the improved learning to exploration (or inquiry).…”
Section: Several Different Types Of Question-based Instruction Have Bmentioning
confidence: 99%
“…Another disturbing development was the dearth of material addressed in some inquiry classes. Cook and Borkovitz (2017) noted that some inquiry-based courses addressed less material than the same classes at other institutions (which used more traditional teaching styles). Other inquiry-based classes addressed topics that were different from those addressed in comparable non-inquiry-based classes.…”
Section: Several Different Types Of Question-based Instruction Have Bmentioning
confidence: 99%